Changes in tapered endotracheal tube cuff pressure after changing position to hyperextension of neck: A randomized clinical trial. Issue 29 (23rd July 2021) - Park, Ji-Hoon; Lee, Hyo-Jin; Lee, Sou Hyun; Kim, Ji Seob
Abstract: Background: Endotracheal tube (ETT) with a tapered-shaped cuff had an improved sealing effect when compared to ETTs with a conventional cylindrical-shaped cuff. Positional change and neck movement typically displace an ETT and change the intracuff pressure. The aim of the current study was to compare the ETT cuff pressure in the TaperGuard ETT vs the conventional ETT after a change from the supine, neutral position to the extension of the neck and semi-Fowler position for thyroid surgery. Methods: This prospective, randomized clinical trial included 50 patients undergoing thyroidectomy. Patients were randomly allocated into one of the 2 groups: tracheal intubation with the TaperGuard ETT or with a conventional ETT. The ETT cuff was inflated with air and the ETT cuff pressure was set initially at 20 cmH2 O using a calibrated cuff manometer. ETT cuff pressure and distance from carina to ETT tip were measured at supine and semi-Fowler positions with neck extension. Results: After the position change, the ETT tip migrated cephalad and cuff pressure increased in the majority of cases. ETT cuff pressure was significantly higher in the TaperGuard group than the conventional group (28.0 ± 6.6 cmH2 O and 22.8 ± 4.5 cmH2 O, respectively, P = .001). The degree of cephalad displacement of the ETT tip was comparable between the 2 groups (19.4 ± 6.31 mm in TaperGuard group and 21.9 ± 6.9 mm in conventional group, P = .12). Conclusions: After the position change from supine to hyperextension of the neck, the ETT cuff pressure was higher in the TaperGuard ETT than in the conventional ETT, although the extent of displacement of the ETT was comparable between the 2 groups.